Exploring hydrophobicity or hydrophilicity of borophene surface via reactive molecular dynamics simulation - Foroutan, Masumeh; Sababkar, Mahnaz; Bavani, Borhan Mostafavi (Scientific reports, 2024)
Borophene, a novel two-dimensional material unveiled in 1998, has garnered significant interest among researchers due to its distinct mechanical and electrical characteristics. Efforts to experimentally synthesize borophene continue to captivate researchers’ interest in recent years. Given the current lack of experimental studies on the interaction between water and the borophene surface, molecular dynamics simulation offers a valuable approach for predicting the substance’s reactivity with water. Additionally, such simulations can assess the hydrophilicity and hydrophobicity of borophene, providing valuable insights into its properties. In our current research, we utilized reactive molecular dynamics simulation to investigate the wetting behavior of borophene. Our findings reveal that the borophene surface exhibits hydrophobic characteristics, demonstrating anisotropic wettability. Specifically, the water contact angle was calculated to be 149.11° along the zigzag direction and 148.4° along the armchair direction. The contour map of the interaction energy between a water molecule and the borophene surface revealed a notable energy barrier in the zigzag direction. This barrier contributes to the asymmetric spreading of the water droplet on the surface. Density profiles and radial pair distribution function (RDF) diagrams of the water droplet on the borophene surface further corroborated the hydrophobic nature of borophene by indicating a significant distance between the water droplet and the surface. Moreover, analysis of the number of hydrogen bonds demonstrated that borophene efficiently utilizes nearly all its capacity to form hydrogen bonds. Additionally, we compared the wettability of borophene with that of other two-dimensional materials, such as various graphene allotropes and phosphorene, which have been subjects of recent investigation.